PELANGGARAN ETIKA PERIKLANAN DI MEDIA DIGITAL ADS STUDI KASUS PADA IKLAN ULTRAMILK GET YOUR POWER BACK - Qori Syamilza Aulia; Daniel Handoko; Mumtazah, Zhahira; Zalfa Putri Salsabila; Raihanda Immanuzaki (CV. Denasya Smart Publisher, 2025)
This study explores ethical violations in digital advertising through a case study of the UltraMilk “Get Your Power Back” campaign. Amid the increasing shift to digital platforms, ethical considerations in advertising have become more complex and urgent. Guided by the Indonesian Advertising Ethics Code (Etika Pariwara Indonesia – EPI), this research analyzes the depiction of children in controversial scenes: a boy stepping on an adult, a girl standing on a chair, and a boy on a tree, all lacking proper educational context. Using a qualitative method with a case study and interpretive paradigm, the study employs semiotic analysis and references theories such as social reality construction, value co-creation, and Barthes' semiotics to interpret visual meanings and social implications. Findings indicate that the ad potentially violates Articles 6, 28, and 38 of the EPI, related to safety, decency, and the responsible use of humor. Although the ad achieves emotional engagement, it raises concerns about reinforcing inappropriate social behaviors among young audiences. The study highlights the need for ethical pre-testing, cultural sensitivity, and clearer regulatory frameworks in digital advertising to ensure messages align with societal norms while maintaining creativity.